The formation of bound residues of diazinon in four UK soils: Implications for risk assessment - Fenlon, Kate; Andreou, Kostas; Jones, Kevin; Semple, Kirk (My University, 2011)
The behaviour of diazinon in the soil determines the likelihood of further pollution incidents, particularly leaching to water. The most significant processes in the control of the fate of diazinon in the soil are microbial degradation and the formation of bound residues. Soils from four sites in the UK were amended with diazinon and its 14C labelled analogue and incubated for 100 days. After 0, 10, 21, 50 and 100 days, the formation of bound residues was assessed by solvent extraction, and the microbial degradation of diazinon by mineralisation assay. In microbially active soils, diazinon is degraded rapidly, reducing the risk of future pollution incidents. However, where there was limited mineralisation there was also significantly lower formation of bound residues, which may lead to water pollution via leaching. The formation of bound residues was dependent on extraction type. Acetonitrile extraction identified bound residues in all soils, with the bound residue fraction increasing with increasing incubation time.
Keywords: Diazinon; Bound residue; Mineralisation; HPCD; Soil